6‐Methyl‐7‐Aryl‐7‐Deazapurine Nucleosides as Anti‐Trypanosoma cruzi Agents: Structure‐Activity Relationship and in vivo Efficacy. (13th May 2021) - Lin, Cai; Ferreira de Almeida Fiuza, Ludmila; Cardoso Santos, Camila; Ferreira Nunes, Daniela; Cruz Moreira, Otacílio; Bouton, Jakob; Karalic, Izet; Maes, Louis; Caljon, Guy; Hulpia, Fabian; de Nazaré C. Soeiro, Maria; Van Calenbergh, Serge
Abstract: Chagas disease is a tropical infectious disease resulting in progressive organ‐damage and currently lacks efficient treatment and vaccine options. The causative pathogen, Trypanosoma cruzi, requires uptake and processing of preformed purines from the host because it cannot synthesize these de novo, instigating the evaluation of modified purine nucleosides as potential trypanocides. By modifying the pyrimidine part of a previously identified 7‐aryl‐7‐deazapurine nucleoside, we found that substitution of a 6‐methyl for a 6‐amino group allows retaining T. cruzi amastigote growth inhibitory activity but confers improved selectivity towards mammalian cells. By keeping the 6‐methyl group unaltered, and introducing different 7‐aryl groups, we identified several analogues with sub‐micromolar antitrypanosomal activity. The 7‐(4‐chlorophenyl) analogue 14, which was stable in microsomes, was evaluated in an acute mouse model. Oral administration of 25 mg/kg b.i.d. suppressed peak parasitemia and protected mice from infection‐related mortality, gave similar reductions as the reference drug of blood parasite loads determined by qPCR, but as benznidazole failed to induce sterile cure in the short time period of drug exposure (5 days). Abstract : A SAR investigation on the pyrimidine part of a previously identified 7‐aryl‐7‐deazapurine nucleoside provided the most promising 6‐methyl analogue against T. cruzi . A series of 7‐aryl‐6‐methyl derivatives was prepared and evaluated, giving rise to several analogues with sub‐micromolar antitrypanosomal activity. Compound 14 was found to be metabolically stable and active against T. cruzi after oral dose of 25 mg/kg b.i.d in an acute mouse model.